Early Neoproterozoic metagabbro-tonalite-trondhjemite of Sør Rondane (East Antarctica): Implications for supercontinent assembly - Elburg, M.; Jacobs, J.; Andersen, T.; Clark, Christopher; Läufer, A.; Ruppel, A.; Krohne, N.; Damaske, D. (Elsevier BV, 2014)
New data for intrusive meta-igneous rocks from the Southwest terrane of the Sør Rondane Mountains confirm the view that this is a juvenile oceanic arc terrane, with the main phase of subduction-related magmatic activity around 995–975 Ma. Younger magmatism (960–925 Ma) is more varied: a high Sr/Y (‘adakitic’) suite is present, as well as high-Ti mafic dykes, and one sample of A-type granite. This is interpreted as reflecting the end of subduction. The occasional presence of Archaean inherited zircons suggests proximity of Sør Rondane to an older continental nucleus from which detritus was shed. Although the ‘meta-igneous sector’ appears to be unique in representing a juvenile oceanic arc terrane, igneous ages and isotopic compositions around 1000–900 Ma suggest a broad coherence between outcrops ranging from Schirmacher Oasis (11° E) to Yamato Mts (35° E). This area seems unrelated to the slightly older, and isotopically and geochemically more enriched Mesoproterozoic rocks of central and western Dronning Maud Land. A closer relation appears to exist with Sri Lanka-India-Madagascar during the earliest Neoproterozoic than with southern Africa.